The Influence of Change Management, Leadership, Corporate Culture on Employee Performance through Work Motivation at PT BPR Buduran Deltapurnama - Dewi, Linda Intania; Firdaus, Vera; Supardi, Supardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
Human resource management and factors such as change management, leadership, and corporate culture play a crucial role in enhancing employee performance through increased motivation. PT BPR Buduran Deltapurnama must focus on these factors to address challenges in the banking industry and maintain competitiveness. The aim of this study is to analyze the influence of change management, leadership, and corporate culture on employee performance through work motivation among the employees of PT BPR Buduran Deltapurnama. This research employs a quantitative approach with a hypothesis testing design. The respondents consist of all 100 employees of PT BPR Buduran Deltapurnama. Data analysis techniques utilize SEM PLS. Employee performance at PT BPR Buduran Deltapurnama can be significantly improved through effective leadership, a strong corporate culture, and efficient change management.